Dynamic Performance Comparison of Conventional and Interleaved Boost Converters under Partial Shading - Jamaluddin Al Rasyid AR, Zya; Al Fama, Novix Jefri (Aceh Journal of Electrical Engineering and Technology, 2026)
Photovoltaic (PV) panels under partial shading experience rapid input voltage changes that disturb maximum power point tracking (MPPT). This study aims to compare the performance of a conventional boost converter (LT3757) and a two‑phase non‑synchronous interleaved boost converter (LTC3787) for a 100 Wp PV system (nominal input 17.7 V, output 24 V). A dynamic simulation was performed in LTspice with input voltage stepping from 17.7 V to 8.5 V (simulating partial shading) and back, while simultaneously switching the load resistance (5.76 Ω for 100 W, 11.52 Ω for 50 W). Measured parameters include input current ripple, efficiency, undershoot, overshoot, and settling time. Results show that the interleaved converter achieves 14% lower input current ripple during the shading transition (6.54 A vs. 7.74 A), much shorter settling time (648 µs vs. 3386 µs), and keeps the output voltage within the ±2% tolerance band throughout the transient, whereas the conventional converter violates the band. Efficiency is nearly identical for both converters (≈96% at 100 W, ≈95% at 50 W). Mathematical analysis reveals that the higher steady‑state ripple of the interleaved converter is due to a ripple cancellation factor of only 0.603 at D=0.284 and the smaller inductors (3.3 μH vs. 6.8 μH). It is concluded that for small‑scale off‑grid PV systems frequently affected by partial shading, the interleaved converter is recommended because of its superior dynamic performance.